Speech of love and marriage. Between social identity and social foundations - KAHLAT, Nedjoua (Journal of Human Sciences, 2020)
This study serves to highlight the implicit potential of language of speakers in a text of a position statement speech. It demonstrates, Thanks to pragmatic interdisciplinary tools analysis′, how a speaker in love and marriage speech represents a social identity which enunciates unspoken that express a position statement speech in front of the fundaments of functioning of his environment. That leads to confirm that in the text, the language of speakers represents the world and acts upon it by conveying implicit which attach legitimacy and an authority in a position statement speech.